Penerapan Cyber Notary terhadap Keabsahan Akta Publisitas Untuk Pendaftaran Badan Hukum - Nanda Pamuji; Muhamad Rafli Nuruddin; Deni Dwi Mahardika (Universitas Batanghari Jambi, 2026)
The purpose of this study is to determine the regulations regarding the registration of legal entities when applied with a cyber notary and to understand the validity or proof of the publicity deeds created for the registration of legal entities thru a cyber notary. Cyber notary is a concept for the electronic execution of a notary's duties, which has sparked both support and opposition from various parties, including practitioners and researchers. This is a dynamic in the implementation of Cyber Notary in Indonesia. The research method used is normative juridical with an approach thru legislation. The research results indicate that the regulation regarding the registration of legal entities thru cyber notaries is based on Article 15 paragraph (3) of the Notary Office Law (UUJN), which allows notaries to obtain other authorities based on the provisions of the law. According to the Minister of Law and Human Rights Regulation (Permenkumham), the legal form of cyber notary is provided only for limited purposes, specifically for submitting applications to use the name of a legal entity, applications for legal entity approval, applications for legal entity announcement, and approval of amendments to the articles of association of a Limited Liability Company. Furthermore, the deed of publicity in the registration of legal entities thru a cyber notary still has strong and perfect evidentiary power, based on Article 15 paragraph (3) of the Notary Law and Minister of Law and Human Rights Regulation Number 2 of 2016 which regulates the registration of legal entities thru the Legal Entity Administration System (SABH) as an electronic legal entity administration service system.